Jellyfish bycatch diminishes profit in an anchovy fishery off Peru - Quiñones Dávila, Javier (2013)
Peru supports one of the world’s largest single-species fisheries based on the Peruvian anchovy (Engraulis ringens L. Jenyns, 1842), and bycatch of the scyphomedusa Chrysaora plocamia (Lesson, 1832) affects this fishery. Medusae display strong seasonal fluctuations, with peak abundances during summer. Off southern Peru and during the austral summer 2008–2009, C. plocamia were >30% of the catch in 5% of the hauls, which was enough to cause economic losses of more than 200,000 US$ in only 35 d of fishing. Fishery factories refused to receive the catch if jellyfish bycatch was >40% ofthe catch in weight. Economic losses could substantially increase during warm periods like El Nino, ˜ during which C. plocamia medusa abundances greatly increase. This study was the first attempt to quantify economic losses due to jellyfish through the use of bycatch rates and interviews with employees of fishery factories